Global Analysis of Nutritional Factors and Cardiovascular Risk: Insights from Worldwide Data and a Case Study in Mexican Children - Karmina Sánchez-Meza; Gustavo A. Hernández-Fuentes; Estibaliz Sánchez-Meza; Ivan Delgado-Enciso; Carmen A. Sánchez-Ramírez; Roberto Muñiz-Valencia; José Guzmán-Esquivel; Idalia Garza-Veloz; Margarita L. Martinez-Fierro; Iram P. Rodriguez-Sanchez; Janet Diaz-Martinez; Joel Cerna-Cortés; et al. (Journal of Cardiovascular Development and Disease)
Cardiovascular diseases (CVDs) are the leading cause of mortality worldwide, with growing concerns about the impact of omega-6 polyunsaturated fatty acids (n-6 PUFAs) on cardiovascular health. This study aims to evaluate the relationship between serum linoleic acid (LA) levels and waist-to-height ratio (WHtR), a recognized cardiovascular risk marker, in children. The research was conducted in two parts. First, a global analysis of publicly available data (2019–2021) explored the association between nutritional factors and CVD prevalence across 183 countries. Second, a cross-sectional study involving 67 children (33 with obesity and 34 with healthy weight, classified using BMI Z-scores) examined the correlation between serum LA levels and WHtR. Global analysis revealed a moderate correlation between low seafood omega-3 fatty acid intake and CVD incidence (rho = 0.341), while low polyunsaturated fatty acid consumption showed a weak correlation (rho = 0.228). In children, a significant positive correlation was observed between serum LA levels and WHtR (rho = 0.716, p < 0.001), with similar correlations found when stratified by sex (girls: rho = 0.690; boys: rho = 0.709). Serum LA levels also correlated positively with weight (rho = 0.684). These findings are consistent with the existing literature, that high serum LA levels may contribute to early cardiometabolic risk in children, emphasizing the need for dietary interventions to mitigate cardiovascular risks in early life.